Lead Fractures in Deep Brain Stimulation during Long-Term Follow-Up - Fernando Seijo Fernández; Marco Antonio Alvarez Vega; Aida Antuña Ramos; Fernando Fernández González; Beatriz Lozano Aragoneses (Parkinson's Disease)
The purpose was to determine the incidence of lead fracture in patients with DBS over a long period of time. We present a retrospective study of 208 patients who received 387 DBS electrodes. Fourteen patients had sixteen lead fractures (4% of the implanted leads) and two patients suffered from 2 lead fractures. Of all lead fractures, five patients had the connection between the leads and the extension cables located in mastoids region, ten in cervical area and one in thoracic region. The mean distance from the connection between the electrode and the extension cable and the lead fracture was 10.7 mm. The lead fracture is a common, although long-term complication in DBS surgery. In our experience, the most common site of electrode cable breakage is approximately between 9 and 13 mm from the junction between the lead and the extension cable. The most important cause of lead fracture is the rotational movement of the lead-extension cable system. If we suspect lead fracture, we must check the impedance of the electrode and to evaluate the side effects of voltage. Finally, we must conduct a radiological screening.